The Impact Of Information Technology Adoption On Employee Productivity In Nongovernemental Organizations In Yemen - Al-Nashmi, Murad Mohammed; Amer, Redhwan Ali (IJSSHR)
The nongovernmental sector plays a vital role in supporting the economic development of a country. This study attempts to evaluate the impact of IT adoption on the employee productivity in nongovernmental organizations. It focuses on the relative importance of information technology adoption factors grouped in the three variables of IT adoption and to ascertain the levels of employee productivity experienced among staff working in nongovernmental organizations in Sana'a, Yemen. For the purpose of this study convenience sampling design was used to assess employee productivity. The sample group (N =138) consisted of staff, managers and IT officers working in nongovernmental organizations. A questionnaire was designed to gather the data. Questionnaire data was collected from 4 nongovernmental organizations located in Hadda area in Sana’a, Republic of Yemen. It measures employee productivity on three IT adoption factors, namely, IT infrastructure, IT innovation and IT knowledge management. Results indicate that staff in nongovernmental organizations showed high employee productivity through three variables: IT infrastructure, IT innovation and IT knowledge management related to IT adoption. Also results show that moderate positive employee productivity is achieved through other three variables of IT adoption: IT infrastructure, IT innovation and IT knowledge management. Finally, results show that the IT knowledge management is the variable which has the most impact on the employee productivity.
Keywords: Employee productivity; IT adoption; IT infrastructure; IT innovation; IT knowledge management; Nongovernmental organizations; Yemen